2014
DOI: 10.1177/1533317514536598
|View full text |Cite
|
Sign up to set email alerts
|

Which Rivastigmine Formula is Better for Heart in Elderly Patients With Alzheimer’s Disease

Abstract: It was demonstrated that rivastigmine formulations were not associated with increased arrhythmogenic or hypotensive effects in elderly patients with AD and was not superior to each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Regarding outcomes, hypertension was defined according to objective measurement in 9 studies. [13][14][15][16][23][24][25][26]33 Bradycardia and heart rate changes were evaluated according to objective measurement in 17 studies, 13,[15][16][17]19,[22][23][24][25][26][27][28][29][30][31]33,34 and one study reported data on bradycardia from a database. 32 After a median follow-up of 24 weeks (range 3-463 weeks), AChEI use was associated with a higher proportion of hypertension in 7 studies compared to baseline (1,573 individuals, 4%, 95% CI52-8%, p<.001, I 2 547%) and bradycardia in 12 studies (13,703 participants, 2%, 95% CI51-6%, p<.001, I 2 598%).…”
Section: Longitudinal Studies Reporting On Changes Over Time In CV Oumentioning
confidence: 99%
“…Regarding outcomes, hypertension was defined according to objective measurement in 9 studies. [13][14][15][16][23][24][25][26]33 Bradycardia and heart rate changes were evaluated according to objective measurement in 17 studies, 13,[15][16][17]19,[22][23][24][25][26][27][28][29][30][31]33,34 and one study reported data on bradycardia from a database. 32 After a median follow-up of 24 weeks (range 3-463 weeks), AChEI use was associated with a higher proportion of hypertension in 7 studies compared to baseline (1,573 individuals, 4%, 95% CI52-8%, p<.001, I 2 547%) and bradycardia in 12 studies (13,703 participants, 2%, 95% CI51-6%, p<.001, I 2 598%).…”
Section: Longitudinal Studies Reporting On Changes Over Time In CV Oumentioning
confidence: 99%
“…At present, treatment of AD is mainly provided with acetylcholinesterase (AChE) inhibitors, compounds which increase the level of acetylcholine in the brain. However, since there are frequent adverse side-effects including hepatic injury, diarrhea, or cardiovascular damage [35], the discovery of new, selective AChE inhibitors is of interest. In this context, many natural products or their derivatives have been found to have AChE inhibitory activity [69].…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable thing about this case is the development of asymptomatic bradycardia due to rivastigmine use. Although ChEIs are safe for the cardiac system, a limited number of case reports indicate development of atrioventricular block during rivastigmine therapy. In one of them, the relationship between development of third‐degree atrioventricular block and rivastigmine therapy could not be demonstrated definitely because cardiac biomarkers were higher than normal in both cases and ischemic etiology could not be fully clarified .…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: Rivastigmine is a reversible cholinesterase inhibitor (ChEI) with demonstrated efficacy in the treatment of Lewy body dementia (LBD), primarily in Alzheimer‐type dementia . Although the brain is the main target organ of rivastigmine therapy, cardiac muscle tissue, which is rich in cholinesterase, could be adversely affected.…”
mentioning
confidence: 99%
See 1 more Smart Citation